2016
DOI: 10.1007/s10653-016-9855-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of tube well water intended for irrigation and human consumption with special emphasis on arsenic contamination at the area of Punjab, Pakistan

Abstract: In the present study, the tube well water quality and the associated health risks, emphasizing on arsenic contamination, were investigated in rural and urban samples from Tehsil Mailsi located in Punjab, Pakistan. Arsenic concentrations (μg/L) were ranged from 12 to 448.5 and which exceeded the WHO recommended limit (10 μg/L) in all cases. The calculated average daily dose (3.3 × 10 to 1.2 × 10 mg/kg day) and hazard quotient (1.1-40) reflected the potential health risk to local population due to tube well wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Excessive use of arsenical pesticides on crops may be a source of arsenic contamination due to leaching process of fertilizers and pesticides from soils to groundwater. The major source of metal pollution in water is use of pesticides in the form of calcium arsenate, lead arsenate, sodium arsenate and arsenic acid (Rasool et al 2016). …”
Section: Iron and Arsenicmentioning
confidence: 99%
“…Excessive use of arsenical pesticides on crops may be a source of arsenic contamination due to leaching process of fertilizers and pesticides from soils to groundwater. The major source of metal pollution in water is use of pesticides in the form of calcium arsenate, lead arsenate, sodium arsenate and arsenic acid (Rasool et al 2016). …”
Section: Iron and Arsenicmentioning
confidence: 99%
“…According to another study, where arsenic concentration in groundwaters of Northern Greece was investigated, this value is realistic and actually is at the lower end of values measured in the arsenic affected ground waters in this region [5]. Values of alkalinity ranged between 4 and 8 mM HCO 3 in this area, and similar or slightly higher concentrations were measured in other areas with arsenic polluted groundwaters, such as in Argentina [24], in the Pannonian basin [25], and in Pakistan [26]. Therefore, since alkalinity is known to affect the efficiency of coagulation, in the present study, alkalinity values from 1 to 8 mM were examined to evaluate the effect on As(III) removal.…”
Section: Effect Of Carbonate Concentration On As(iii) Removal By the mentioning
confidence: 51%
“…The PAK-EPA surveys reported more alarming figures for As in ground water and found 12-488 (µg L -1 ) As concentration in drinking water in Tehsil Mailsi, Punjab. These amounts are far greater than the permissible limit (10 µg L -1 ) by WHO (Rasool et al 2017). Afzal et al (2014) reported enhanced concentrations of Cd (37 mg kg -1 ) and Cr (2443 mg kg -1 ) in soils of Kasur, Punjab, Pakistan where industrial wastewater was used for irrigation.…”
Section: Introductionmentioning
confidence: 91%